IMPROVING STUDENTS' MOTIVATION TO LEARN ENGLISH IN PRIMARY SCHOOL - Roni Roni; Sam Hermansyah (Indonesian Journal of Education (INJOE), 2023)
The most crucial element for educators to consider when trying to enhance learning is motivation. Many educators have contributed their research on how to increase students' motivation. One of the most crucial goals on a daily basis is it. Students who are conceptualized learn, perform well in job, have a strong desire to get involved and motivated, and succeed in school. This essay discusses the traits of primary pupils, the function of the primary English teacher, and the methods used by teachers to inspire students to learn English. Getting kids motivated can be done in three different ways: extrinsic, intrinsic, and group motivation. It is determined that TPR, using songs, and playing games are effective techniques for kids to develop intrinsic motivation. Achieving extrinsic motivation is divided into "external regulation, interjected regulation, and identified regulation" depending on how powerful or weak it is. The last factor is group motivation, which is highly significant in language teaching that takes place in the classroom. Therefore, it is advisable for English teachers in elementary schools to foster an environment where students feel motivated and engaged.